Electrical properties of flash-processed (Mg, Co, Ni, Cu, Zn)O high entropy oxide - Gautam A.; Chaubey S.; Saurabh; Verma H.; Urkude R.; Ahmad M.I. (My University, 2025)
This study highlights the importance of defect generation and electrochemical reduction during flash sintering, which affects the formation of high entropy phase and electrical properties. We synthesized and densified phase pure rocksalt five component (Mg, Co, Ni, Cu, Zn)O high entropy oxide (HEO), at 350 ℃ via flash sintering under the electric field varying from 50 to 200 V/cm and achieved up to 96% density. Defect generation during flash processing was analysed by investigating the local structure and oxidation state of the elements, and its effect on dielectric properties and electrical conductivity was studied. An increase in dielectric constant and shift in loss tangent peak was observed, indicating a change in the polarization mechanism in flash-processed samples. Conventionally sintered (Mg,Co,Ni,Cu,Zn)O HEO samples generally show dominant electronic conductivity; however, on flash sintering, mixed ionic and electronic conductivity was observed, which indicates that defect generation plays an important role during flash processing. © 2025 Elsevier Ltd